Mengatasi Neck pain pada Pekerja Cuci Mobil: Studi Kasus Edukasi Fisioterapi di Mulya Carwash Samarinda - Fatmarianni; Nurul Aini Rahmawati (Rena Cipta Mandiri, 2025)
Introduction: Neck pain is one of the musculoskeletal disorders that is often experienced, especially by workers who do heavy physical activities, such as car wash workers. This condition can interfere with the quality of life and work productivity. Objective: This study aims to provide physiotherapy education on the prevention and treatment of neck pain using static stretching and self-stretching methods. Method: The method used is one group pre-posttest, where 21 participants from Mulya Carwash Samarinda took a pretest to evaluate their understanding of neck pain before education. During the counseling, participants were given material on the definition, risk factors, signs and symptoms, and self-stretching techniques that can be done independently. Conclusion: The results of the study showed a significant increase in participants' understanding of the prevention and treatment of neck pain, this educational activity succeeded in providing insight and skills to workers to prevent and treat neck pain independently, which has the potential to improve their quality of life and productivity.